2019
DOI: 10.1103/physrevb.99.134505
|View full text |Cite
|
Sign up to set email alerts
|

Tunable magnetic textures in spin valves: From spintronics to Majorana bound states

Abstract: Spin-valve structures in which a change of magnetic configuration is responsible for magnetoresistance led to impressive advances in spintronics, focusing on magnetically storing and sensing information. However, this mature technology also offers versatile control of magnetic textures with usually neglected underlying fringing fields to enable entirely different applications by realizing topologically-nontrivial states. Together with proximity-induced superconductivity in a two-dimensional electron gas with a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 83 publications
(126 reference statements)
1
42
0
Order By: Relevance
“…Therefore, there has been an increasing interest in the use of magnetic textures for the generation of MBS [29][30][31][32][33][34][35][36][37][38][39][40][41]. In particular, the use of locally tunable magnetic fringing fields can enable the realization of both braiding and fusion operations [42][43][44]. The suitability of using synthetic SOC generated by magnetic fringing fields for the creation of MBS in a superconducting carbon nanotube has recently been experimentally demonstrated [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there has been an increasing interest in the use of magnetic textures for the generation of MBS [29][30][31][32][33][34][35][36][37][38][39][40][41]. In particular, the use of locally tunable magnetic fringing fields can enable the realization of both braiding and fusion operations [42][43][44]. The suitability of using synthetic SOC generated by magnetic fringing fields for the creation of MBS in a superconducting carbon nanotube has recently been experimentally demonstrated [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…A push to seek alternative platforms for topological superconductivity led to the demonstration of robust proximityinduced superconductivity in a two-dimensional electron gas (2DEG) [18][19][20] which offers important opportunities to realize and control MBS [21][22][23][24][25][26][27]. Recent experiments in planar Josephson junctions (JJs) [28][29][30] reveal that topological superconductivity exists over a large parameter space without requiring fine tuning, while demonstrating the key role of superconducting phase to control the topological transition.…”
mentioning
confidence: 99%
“…For example, state-of-the art fabrication of superconducting junctions with topological insulators [38] would support fabrication of similar X-shaped junctions. With the progress in tunable magnetic textures used to modify proximity-induced superconductivity [23,27,[39][40][41][42][43][44][45][46][47][48][49], X-shaped junctions could be considered with a reduced role of an applied magnetic field.…”
mentioning
confidence: 99%
“…While the latter can change with increasing magnetic field 17 , the existence of topological phases in skyrmion MSH systems is robust against these changes. Our results present the extension to 2D topological superconductors of recent work [32][33][34] which demonstrated that the manipulation of non-collinear magnetic textures imposed on a 2D superconductor-either through the application of an external magnetic field 32 or current 33 , or through quantum engineering 34 -can give rise to a one-dimensional topological superconductor exhibiting localized Majorana zero modes at its ends. Moreover, skyrmion MSH systems provide a unique opportunity to employ JSTS to visualize a necessary requirement for the emergence of topological superconductivity, the existence of induced spin-triplet superconducting correlations.…”
Section: Msh System With a Skyrmion Ribbonmentioning
confidence: 58%